Promotion strategies of food delivery O2O supply chain with anti-food waste regulation - Xu, Guangye; Tang, Yan; Xu, Shiqi (Frontiers in Sustainable Food Systems, 2024)
This paper connects food waste with food delivery service and aims to explore the impacts of the anti-food waste regulation on food waste generation and the selection of promotion strategy in an Online-to-Offline (O2O) supply chain. Using a game-theoretical approach, we focus on three prominent promotion strategies—a no-promotion strategy (N strategy), a price discount strategy (D strategy), or a volume-based price discount strategy (S strategy). Our research results indicate that the restaurant’s choice of promotion strategy is almost independent of the intensity of anti-food waste penalties. However, the optimal strategy of the platform and the amount of waste are influenced by it. Under certain conditions, restaurants and platforms were able to achieve a win-win situation through promotion strategies. In the case of the relaxation of anti-food waste regulations, both restaurants and platforms tend to adopt the D strategy. In contrast, when penalties are stronger, platforms may be forced to accept D or S strategy because of the proactive behaviors of restaurants, even if they would prefer not to adopt promotion strategies. Overall, the government should consider bringing restaurants under regulation to protect platform revenue and effectively reduce food waste.